2019
DOI: 10.1002/jcla.23145
|View full text |Cite
|
Sign up to set email alerts
|

Widespread of non‐typeable Haemophilus influenzae with high genetic diversity after two decades use of Hib vaccine in China

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: The aim of this study was to analyze the microbiological characteristics of nasopharyngeal carriage Haemophilus influenzae isolates collected from children with respiratory infections in Beijing hospital and Youy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
2
15
2
Order By: Relevance
“…However, in our study, 18 isolates of BLNAR were identified from 196 test isolates (9.2%). A former report in Shanghai, China, and Beijing, China, the detection rate of BLNAR strains was 11.76 and 18.9% ( 24 , 25 ). In other countries, especially, Japan, BLNAR strains prevalence was >40% ( 3 ).…”
Section: Discussionmentioning
confidence: 85%
“…However, in our study, 18 isolates of BLNAR were identified from 196 test isolates (9.2%). A former report in Shanghai, China, and Beijing, China, the detection rate of BLNAR strains was 11.76 and 18.9% ( 24 , 25 ). In other countries, especially, Japan, BLNAR strains prevalence was >40% ( 3 ).…”
Section: Discussionmentioning
confidence: 85%
“…H. influenzae remains a common cause of illness in children worldwide and account for a considerable proportion of deaths due to bacterial pneumonia ( 2021 ; Dong et al., 2020 ; Fu et al., 2021 ). Better access to rapid, effective, and reliable laboratory diagnosis is needed especially for definitive clinical diagnosis and timely treatment, which has a positive impact on the course of the infection ( Shooraj et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, H. influenzae could infect various parts of the human body, causing diseases such as meningitis, epiglottis, and septic arthritis ( Marrs et al., 2001 ; Shooraj et al., 2019 ; Fu et al., 2021 ). Children aged from 2 months to 5 years old were more susceptible to H. influenzae infections because of the incapacity of transplacental maternal antibodies to the newborns and the lack of “natural antibodies” for the older children and the adults ( Ladhani et al., 2012 ; Dong et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although H. influenzae typically colonizes the respiratory tracts, it has been reported that a few women might carry NTHi in their genital tracts [12]. The comparatively widespread nature of NTHi consequent to the use of Hib vaccine in recent years emphasizes the need to familiarize ourselves with this important pathogen [7,8]. Our present case not only involved a rare occurrence of an invasive H. influenzae infection associated with adenomyosis, but also presents several lessons for those dealing with infectious disease in their daily practices.…”
Section: Discussionmentioning
confidence: 99%
“…Although H. influenzae type b (Hib) is a notoriously virulent serotype of this species [4], the introduction of routine conjugate Hib vaccination led to a decrease in the number of cases of Hib infection [5]. Over the past decades, however, this decrease was paralleled by an increase in the frequency of non-typable H. influenzae (NTHi) infection, which now accounts for the majority of invasive H. influenzae infection cases [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%